Motivational pathways for farmer learning behaviour in the student‐to‐farmer university outreach - Kalule, S.W.; Sseguya, H.; Karubanga, G.; Ongeng, D. (Wiley, 2023)
In recent times, calls for practical training of agricultural extension workers, who exhibit the right mix of competences for responsiveness to farmer learning needs, have intensified. This comes at the time when there is an increasingly growing desire for more community‐engaged African universities, and as such, making the integration of agricultural students into community outreach services a necessity. However, empirical evidence on whether student‐led outreach and training models adequately respond to the psychological learning needs of host farmers and subsequent motivation of these farmers for learning is lacking. This study uses a structural equation modelling technique on a sample of 283 farmers who had previously participated in the student‐to‐farmer outreach of Gulu University. Results reveal that satisfying farmer learning needs influences intrinsic motivation, formation of learning intentions and farmer learning behaviour. Intrinsic motivation mediates the relationship between satisfying farmer learning needs and the outcome learning behaviour. We conclude that satisfying farmer learning needs is a strong initiator of motivational pathways for farmer learning behaviour in the student‐to‐farmer university outreach. We call for more public financing of university outreach programmes so as to enable not only training for churning out graduates with the right competences of responsiveness to community needs but also fostering creative innovations involving both universities and communities.